2006
DOI: 10.1007/s10209-006-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

An alternative approach to strengthening tactile memory for sensory disabled people

Abstract: Deaf and hearing-impaired people need special educational and developmental tools to support their social inclusion. Research in vibro-tactile pattern perception has shown that tactile memory could be a crucial aspect in coding and imaging semantic information for users with sensory limitations. This paper describes a simple matching game designed to facilitate the learning process of 27 vibro-tactile composite patterns (tactons) which can be produced with the Logitech tactile feedback mouse. The underlying as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…Tactile interfaces have been designed to support blind users when interacting with graphical interfaces, by enabling users to 'visualize' information through their sense of touch. Research also suggests that tactile stimuli are known to be memorable over both short and long periods [11,17], providing a discrete means of presenting information to the user. In this paper, we examine the feasibility of tactile stimuli presented within a timed sequence, to support the non-visual authentication process.…”
Section: The Need For An Accessible Solutionmentioning
confidence: 99%
“…Tactile interfaces have been designed to support blind users when interacting with graphical interfaces, by enabling users to 'visualize' information through their sense of touch. Research also suggests that tactile stimuli are known to be memorable over both short and long periods [11,17], providing a discrete means of presenting information to the user. In this paper, we examine the feasibility of tactile stimuli presented within a timed sequence, to support the non-visual authentication process.…”
Section: The Need For An Accessible Solutionmentioning
confidence: 99%
“…Several recent studies show that games have positive influences on learning, particularly on the structuring of knowledge (Evreinova et al, 2006;Lennon & Coombs, 2006;Shaftel et al, 2005).…”
Section: Cognitive Skillsmentioning
confidence: 99%
“…Studies have shown that games (computer, video, serious, classic) reinforce or improve the structuring of knowledge. Some studies conclude that games have positive results on the "structuring of knowledge" (e.g., Evreinova et al, 2006;Lennon & Coombs, 2006;Lieberman, 1998Lieberman, , 2001Mondozzi & Harper, 2001;Rosas, Nussbaum, Cumsille, Marianov, Correa, Flores, et al, 2003). They mention specifically that the participation of the learner in the game improves or reinforces their knowledge of the subject matter at hand.…”
Section: Structuring Of Knowledgementioning
confidence: 99%
“…Using a range of tactile rendering techniques, the researchers created a set of discernable effects, which the user can explore using his/her sense of touch, to locate matching stimuli. Evreinova et al [6] developed a memory game targeted to the needs of deaf and hard of hearing users, where participants explore vibrotactile patterns using the Logitech IFeel mouse [14]. The parameters of frequency and duration were modified to develop the set of effects for the game.…”
Section: Non-visual Gamesmentioning
confidence: 99%